Faktor yang mempengaruhi cash flow perusahaan - Aminah, Wiwin; Audia Putri, Stefany (Jurnal Riset Pendidikan Ekonomi, 2024)
The aim of this research is to identify the impact that cash flow, leverage, and company size have on the company's cash savings. Through the sampling method, using library study data collection techniques with data collection through the necessary reports. The technique used in this research uses panel data regression analysis. Based on the sample selection criteria determined in this research, this study conducted observations on 14 entities in the transportation and logistics sector listed on the Indonesia Stock Exchange in the 2017-2021 period. The data analysis approach used in this research is panel data regression analysis to obtain better research estimation results. The research results confirm that cash flow has a positive influence on cash savings, while leverage and company size do not affect cash savings. These findings reveal that the company utilizes positive cash flow to maintain the company's liquidity. Meanwhile, the company does not depend on debt and company size to carry out the company's operational activities.